1995
DOI: 10.1002/jsfa.2740690305
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting in vitro formation of tannin‐protein complexes

Abstract: In interaction of condensed tannins from Desmodium intortum and Lotus pedunculatus and tannic acid (hydrolysable tannin) with salivary mucoproteins (from sheep and goats), plant leaf proteins and bovine serum albumin were evaluated. These studies were carried out over a p H range of 2.0-9.0 and different inorganic ion conditions to simulate conditions in which dietary proteins would interact with tannins in a ruminant digestive tract. Insoluble tanninprotein interactions were found at pH 4.5-5.5 for bovine ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 37 publications
4
49
1
2
Order By: Relevance
“…Neither puriÐed CT from quebracho nor hydrolysable tannins from TA precipitated AALP at either protein level. These results agreed with those of Perez-Maldonado et al (1995), who found that more plant leaf protein was precipitated by CT from Desmodium intortum and L otus pedunculatus than by TA when samples were incubated in a ruminal environment. TA and puriÐed CT from quebracho precipitated more BSA than puriÐed CT from forages.…”
Section: Experiments 1 Precipitation Of Protein From Bsa and Aalp By supporting
confidence: 94%
“…Neither puriÐed CT from quebracho nor hydrolysable tannins from TA precipitated AALP at either protein level. These results agreed with those of Perez-Maldonado et al (1995), who found that more plant leaf protein was precipitated by CT from Desmodium intortum and L otus pedunculatus than by TA when samples were incubated in a ruminal environment. TA and puriÐed CT from quebracho precipitated more BSA than puriÐed CT from forages.…”
Section: Experiments 1 Precipitation Of Protein From Bsa and Aalp By supporting
confidence: 94%
“…Their response to drying more closely resembled the forage samples studied by Mahyuddin et al [13]. In particular, crude protein digestibility was found to be zero in three of the conserved samples and much reduced in others, implying the formation of a more stable complex than is typical of tannin-protein interactions [20] It was suggested previously that removal of leaves from twigs and branches had a negative effect on both OMD and CPD [8]. Although removal of leaves might, in the short term, promote autolysis and loss of cell content, there is little to suggest that this is significant in the longer term.…”
supporting
confidence: 66%
“…The contents were reduced in the period of ensiling, and may relate to the formation of tannin-protein complexes. Maldonado et al (1995) reported that insoluble tannin and plant leaf protein complex was established in the pH range of 3.5-5.5. In ensiling sorghum, Rodriguez et al (1998) reported that tannin concentration decreased with increase in the duration of fermentation.…”
Section: Discussionmentioning
confidence: 99%